Bowel stiffness associated with histopathologic scoring of stenosis in patients with Crohn's disease. (August 2021) - Zhao, Jingbo; Liao, Donghua; Wilkens, Rune; Krogh, Klaus; Glerup, Henning; Gregersen, Hans
Abstract: Background and aims : Intestinal stenosis is a common complication of Crohn's Disease (CD). Stenosis is associated with alteration of bowel mechanical properties. This study aims to quantitate the mechanical properties of the intestinal stenosis and to explore associations between histology and mechanical remodeling at stenotic intestinal sites in CD patients. Methods : Intestinal segments from stenotic sites were studied in vitro from 19 CD patients. A luminal catheter with a bag was used to stepwise pressurize the intestinal segments from 0-100 cmH2 O with 10 cmH2 O increments. B-mode ultrasound images were obtained at the narrowest part of the stenosis at each pressure level and morphometric parameters were obtained from ultrasound images. The mechanical behavior of the stenotic tissue were characterized by using an isotropic three dimensional strain energy function in Demiray model form, the mechanical constants were obtained by fitting the model to the recorded intraluminal pressure and the inner radius of the stenotic segment of the small bowel. Grading scores were used for histological analysis of inflammation, fibrosis, muscular hypertrophy and adipocyte proliferation in the intestinal layers. The collagen area fraction in intestinal layers was also calculated. Associations between histological and the mechanical constants (stiffness) were analyzed. Results : Chronic inflammation was mainly located in mucosa whereas fibrosis was found in submucosa. The mechanical remodeling was performed with changed mechanical constants ranged between 0.35-13.68kPa. The mechanical properties changes were associated mainly with chronic inflammation, fibrosis and combination of inflammation and fibrosis (R>0.69, P<0.001). Furthermore, the mechanical properties correlated with the collagen fraction in submucosa and muscular layers (R>0.53, P<0.05). Conclusions : We quantitated the intestinal stenosis stiffness. Associations were found between bowel mechanical remodeling and histological changes at the stenotic site in CD patients. Statement of significance: Although intestinal ultrasonography, CT and MRI can be used to diagnose Crohn's Disease (CD)-associated bowel strictures, these techniques may not have sufficient accuracy and resolution to differentiate predominantly inflammatory strictures from predominantly fibrotic strictures. The present study aims to quantitate the mechanical remodeling of intestinal stenosis and to explore the associations between histological parameters and mechanical properties at the intestinal stenotic sites in CD patients. For the first time, we quantitatively demonstrated that the mechanical properties of the intestinal wall in CD stenosis are associated with the chronic inflammation, fibrosis and collagen fraction in the intestinal layers. The results of this study may facilitate design and development of artificial biomaterials for gastrointestinal organs. The potential clinical implication of this study is that the histological characteristics in patients with CD can be predicted clinically by means of inflammation and fibrosis assessment in conjunction with tissue stiffness measurement. Graphical abstract: Image, graphical abstract